THE ROLE OF INSTAGRAM FILTERS IN BUILDING ADOLESCENT CONFIDENCE AT UIN NORTH SUMATRA - Hamdi Al Hafidz; Dika Sahputra; Yulinda Rahma Wardani; Devi YuliantiYulianti (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
As technology develops, it has various kinds of impact on social media. Instagram social media is very much in demand by the whole community, especially teenagers. Teenagers start to feel confident because of the instagram filter that makes the face look more beautiful and handsome so that teenagers can upload photos and videos from the filter results. Esharaghi et.al say, self-confidence is a combination of one’s attitudes and beliefs in dealing with tasks or work that are internal, very relative and dynamic and largely determined by their ability to initiate, carry out, and complete a job. Self-confidence will affect ideas, intentions, initiatives, creativity, courage, perseverance, enthusiasm to work and enthusuasm to work. Therefore, this study was conducted to determine the role of instagram filters in shaping adolescent self confidence. The method used in the study is a qualitative method using interview techniques and field observations. Subjects in this study amounted to 19 people. Based on the results of research that has been carried out by researchers that the role of instagram filters in shaping the selfconfidence of adolescents at UIN North Sumatra. The conclusion given in this study is that a filter can form and increase self-confidence in society, especially in adolescents. The advice that can be given is self-confidence in teenagers, not only because of the instagram filter but also because of publik speaking.